Intradiploic Epidermoid Cyst of the Posterior Fossa – Case Report and Review of the Literature - Januário, Gonçalo; Cunha, Bruno; Cellini, Ludovica; Novais, Gonçalo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Intracranial epidermoid cysts represent ∼ 0.2 to 1.8% of all intracranial tumors. These tumors are most frequently encountered in the cerebellar pontine angle or in the parasellar region. Rarely, they arise from the cranial diploe, being able to affect every flat bone of the cranium.We report a case of a 63-year-old male who presented with progressively worsening headache and vertigo with 6 months of evolution. Neuroimaging identified a probable occipital intradiploic epidermoid cyst with mass effect on the cerebellar hemispheres. This lesion was approached using a suboccipital craniotomy, followed by total resection of the tumor and cranioplasty with titanium plate placement. The histological evaluation confirmed the diagnosis of intraosseous epidermoid cyst. The patient had a successful recovery, without complications or neurologic dysfunction.Being benign lesions, commonly remaining asymptomatic and rarely presenting as a bony lump in the skull bone, it could be straightforward to assume a conservative management with planned follow-up. On the other side, a more aggressive strategy with surgical excision has been advocated, especially in lesions that tend to enlarge and erode the cranial bone with possible consequent epidural extension and mass effect symptoms. A preoperative diagnosis is extremely helpful in proper surgical planning. Diffusion weighted imaging facilitates a straightforward diagnosis.As was observed in our case, the largest reviews on intradiploic epidermoids available in the literature mostly demonstrated a benign clinical course. However, malignant transformation can occur. Some patients develop permanent neurologic deficits from mass effect or tumor infiltration. However, surgical approach of the tumor is curative in most cases. Nonetheless, from our experience, it is important to maintain clinical and imaging follow-up with regular monitoring to prevent possible tumor recurrences.
Keywords: epidermoid cyst; craniotomy; cranioplasty; titanium mesh